Science Process Skills Analysis of Junior High School Students in South Sumatera Using Test Basic of Process Skill (BAPS) - Hartono Hartono; Rahmi Susanti; Melly Ariska (Postgraduate, University of Mataram, 2022)
Basic Science Process Skills (BAPS) are some of the scientific skills used to obtain, process, build and apply scientific theories. Basic science process skills are not only useful in learning science but also for students' daily lives. Therefore, it is very important to master science process skills from the age of teenagers who are in the Junior High School phase. This analysis aims to obtain a profile description of the basic science process skills of Junior High School students. The research method used is descriptive method with research subjects as many as five Junior High Schools in South Sumatra Province as many as 505 students as samples. The data collection technique used is a test technique using 25 questions about the basic ability test of the science process. The data were obtained directly from the VIII grade Junior High School students, after the data were recapitulated and then analyzed by simple statistical analysis. Based on the results of the research that has been carried out, it can be seen that the BAPS ability in junior high schools in South Sumatra Province as a whole is in the medium category, which has a percentage for the overall indicator is 56%. which are 72.3 and 61.12, respectively, so that there is a gender effect on the BAPS ability of junior high school students in South Sumatra Province. Science process skills of junior high school students in South Sumatra Province are based on each indicator, the indicator that has the highest value is the predictive indicator with a percentage of 69% in the medium category and the lowest science process skill indicator is the observing indicator with a percentage of 41.3% in the low category, for science process skills on indicators of concluding and communicating have a percentage of 59.5% and 64.6% respectively in the medium category, science process skills for classifying indicators have a percentage value of 48.9% in the low category.